Evaluasi Program Pendidikan Profesi Guru Menggunakan Model CIPP pada Lingkup Kementerian Agama di Kabupaten Sumba Barat Daya - Lede, Yohanes Umbu; Njuma, Hendrikus Kota; Wandut, Wilhelmina Kurnia; Lede, Imelda Vitrisia (Ideas Publishing, 2024)
The quality of education is determined by educators, teaching materials, methods, and objectives of implementing competency-based education outputs, but in reality there are still many teachers who do not have sufficient competence in carrying out their teaching duties in schools. The purpose of this research is to evaluate the implementation of the PPG program within the scope of the Ministry of Religion office in South West Sumba district. The inner method used in this study is qualitative descriptive research conducted directly in the field (field research) and using the CIPP model approach. The results showed that teachers who participated in PPG experienced an increase in pedagogic and professional competence.